EVALUATIVE SKILLS (C5) IN ISLAMIC CREED AND MORALS EDUCATION: THE EFFECTINESS OF THE TWO STAY TWO STRAY - Della Aprilia; Agus Pahrudin; Riyan Terna Kuswanto; Baharudin Baharudin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study addresses students’ low evaluative (C5) abilities in Akidah Akhlak learning and aims to examine the effectiveness of the Two Stay Two Stray cooperative learning model in improving the evaluative skills of eighth-grade students at MTs Negeri 1 Lampung Selatan. The study employed a quantitative quasi-experimental post-test only control group design, involving class VIII E as the experimental group taught using the Two Stay Two Stray model and class VIII G as the control group receiving conventional instruction. Data were collected using a validated and reliable multiple-choice test. Statistical analysis revealed a significant difference between groups, as indicated by the Mann–Whitney U test (U = 316.000; Z = −2.840; p = 0.005). This result was supported by the Independent Samples t-test (equal variances not assumed), which showed a significant mean score difference of 0.91 in favor of the experimental group (t = −3.064; p = 0.004), demonstrating the effectiveness of the Two Stay Two Stray learning model.